A framework for analysing and informing Australia's National strategic natural resource management policies. Issue 3 (3rd July 2021) - Samnakay, Nadeem
ABSTRACT: Over the past three decades, the Australian Government has led the coordination and implementation of strategic policies that aim to manage natural resources sustainably. Strategic policies typically seek to manage the consumptive use of natural resources to improve a range of environmental variables. This article focuses on strategic policies which operate under national arrangements where the Australian Government has limited direct constitutional powers to regulate natural resource use, so resorts to indirect measures and financial incentives. While the extent to which such policies give effect to sustainable development principles is debatable, as is their appropriateness for achieving environmental gains, a number of strategic natural resource management policies have persisted in the national policy domain. These present opportunities for understanding good-practice policy-making for managing natural resources sustainably, and an evaluative framework is presented to this effect. Relevant inter-relationships and complexities for policy design and implementation are revealed with the intent of stimulating further enquiries and analyses of strategic NRM policies in the context of Australia's federal system.